2020
DOI: 10.1016/s0140-6736(20)30309-3
|View full text |Cite
|
Sign up to set email alerts
|

2019-nCoV epidemic: address mental health care to empower society

Abstract: Objective: The study was conducted to investigate the impact of unrealistic optimism on the risk of contamination at home con nement and its association with certain social variables. Methods: This survey study was conducted to describe the level of unrealistic optimism and its association with some social variables. The participants (n = 558, 60.6% females and 39.4 males) subjectively evaluated the risk of their coronavirus infection in the period 1-15 May 2020, for this purpose a questionnaire was adopted an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

33
1,441
2
143

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,735 publications
(1,753 citation statements)
references
References 1 publication
33
1,441
2
143
Order By: Relevance
“…It has been indicated that the increasing number of patients and suspected cases, as well as the increasing number of provinces and countries affected by the outbreak, have elicited public worry about being infected in this outbreak, which has increased anxiety (Bao et al, 2020). Furthermore, the significant shortage of masks and disinfectants, the overwhelming and sensational news headlines, and erroneous news reports have also added to anxiety and fear (Ayittey et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been indicated that the increasing number of patients and suspected cases, as well as the increasing number of provinces and countries affected by the outbreak, have elicited public worry about being infected in this outbreak, which has increased anxiety (Bao et al, 2020). Furthermore, the significant shortage of masks and disinfectants, the overwhelming and sensational news headlines, and erroneous news reports have also added to anxiety and fear (Ayittey et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The novel coronavirus (COVID-2019) has spread very rapidly all over China and several other countries, causing an outbreak of acute infectious pneumonia (Bao et al, 2020). According to the official website of the National Health Commission of China, there were 49824 confirmed cases (including 9915 severe cases) and 3434 suspected cases of COVID-19 in China as of 23 February 2020 (National Health Council, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 epidemic in China has ignited another epidemic of stress, anxiety and depression (Bao et al, 2020). Since the outbreak of COVID-19, the Chinese government has taken proactive measures to contain not only the spread of the novel coronavirus but also that of psychological distress in the public.…”
Section: Rethinking Online Mental Health Services Inmentioning
confidence: 99%
“…This pandemic is a potential source of direct and vicarious traumatization for everyone (Z. , which is only further emphasized by unsettling case reports of suicide deaths related to fears of contracting or spreading COVID-19 (Goyal et al, 2020;Montemurro, 2020). Therefore, several groups have rightfully called for the development and implementation of mental health screening and intervention programs for both the public and for healthcare workers (Bao et al, 2020;Xiang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%